Notes on the Constitution and gender-inclusive language (Forum, 2022)
This article reviews the “Report on Gender Inclusive Language in the Spanish Constitution” published by the Royal Spanish Academy in 2020, and analyses whether its findings are appliable to the Argentinean Constitution. The article concludes that there are no legal or linguistic grounds for a constitutional amendment since the language employed by the constituents, i.e. the generic male form, is already inclusive of both male and female sexes.
Keywords: Constitutional Law; National Constitution; Gender; Inclusive Language; Lawmaking; Constitutional Amendment